2005
DOI: 10.1124/jpet.105.087742
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment with d-myo-Inositol Trisphosphate Reduces Infarct Size in Rabbit Hearts: Role of Inositol Trisphosphate Receptors and Gap Junctions in Triggering Protection

Abstract: Pretreatment with D-myo-inositol-1,4,5-trisphosphate hexasodium (D-myo-IP 3 ), the sodium salt of the second messenger inositol 1,4,5-trisphosphate (IP 3 ), is cardioprotective and triggers a reduction of infarct size comparable in magnitude to that obtained with ischemic preconditioning. However, this observation is enigmatic; whereas IP 3 signaling is conventionally initiated by receptor binding, IP 3 receptors are typically considered to be intracellular, and D-myo-IP 3 is membrane-impermeable. We propose t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
21
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 42 publications
5
21
1
Order By: Relevance
“…Experiments were conducted by using the isolated buffer-perfused rabbit heart model of regional ischemia (2,6,10,24). In brief, New Zealand White rabbits weighing 2.5-3.5 kg were anesthetized with an intramuscular injection of ketamine plus xylazine (150 mg and 100 mg, respectively).…”
Section: Surgical Preparationmentioning
confidence: 99%
See 3 more Smart Citations
“…Experiments were conducted by using the isolated buffer-perfused rabbit heart model of regional ischemia (2,6,10,24). In brief, New Zealand White rabbits weighing 2.5-3.5 kg were anesthetized with an intramuscular injection of ketamine plus xylazine (150 mg and 100 mg, respectively).…”
Section: Surgical Preparationmentioning
confidence: 99%
“…This was preceded by an intervention period, during which hearts were allocated into 15 treatment groups (n ϭ 6 -8 hearts/group). Five groups of hearts were randomly assigned to receive D-myo-Ins(1,4,5)P3 (CalBiochem, La Jolla, CA), dissolved in 5 ml buffer and administered over 1 min, beginning 25 min before the onset of coronary artery occlusion, via a sidearm located immediately proximal to the heart (final concentration in perfusate was 6 M) (10,24). This dose and timing of D-myoIns(1,4,5)P 3 treatment was shown in early pilot studies to trigger optimal protection in this model (data not shown).…”
Section: Surgical Preparationmentioning
confidence: 99%
See 2 more Smart Citations
“…However, in a recent detailed characterization of its effects on vascular smooth muscle cells (Matchkov et al, 2004), it was shown that heptanol, over the range of concentrations used in our study (0.5-2.0 mM), potently increased the input resistance of the cells and desynchronized their [Ca 2+ ]i oscillations, indicating that it powerfully uncoupled the cells. Indeed, in several recent studies carried out on a range of cell / tissue preparations, including mouse heart (Knapp et al, 2005), rabbit heart (Przyklenk et al, 2005), bovine oocytes (Atef et al, 2005), ciliary body (Do et al, 2004), and human HeLa cells (Bader and Weingart, 2004), heptanol has been either shown (Knapp et al, 2005;Atef et al, 2005) or assumed (Do et al, 2004;Bader and Weingart, 2004) to act as a specific gap junction blocker over a range of concentrations (≤ 10 mM), substantially larger than those used in our study (≤ 2 mM). In our own studies on mammalian vas deferens, the concentrations of heptanol employed to study the effects of uncoupling have not been found to affect resting potential (guinea-pig vas deferens: Manchanda and Venkateswarlu, 1997; rat vas deferens: Palani and Manchanda, unpublished observations), indicating a lack of effect on membrane ion channels.…”
Section: Role Of Cell-to-cell Coupling In Na-induced Contractionmentioning
confidence: 95%